Соглашение o международной дорожной перевозке опасных грузов (ДОПОГ): Действует с 1 января 2023 года - United Nations Economic Commission for Europe (United Nations, 2023)
The ADR is a regulatory instrument that applies to international transport in 53 countries. it applies to national transportation by road in many countries (in particular the countries of the European Union). The ADR lays down requirements for transport operations, driver training and the construction and approval of vehicles. The 2023 edition has been prepared on the basis of amendments which are set to enter into force on 1 January 2023, after acceptance by the Contracting Parties. (Two-volume Set)